2022
DOI: 10.3389/fpls.2022.899681
|View full text |Cite
|
Sign up to set email alerts
|

RAD-Seq-Based High-Density Linkage Maps Construction and Quantitative Trait Loci Mapping of Flowering Time Trait in Alfalfa (Medicago sativa L.)

Abstract: Alfalfa (Medicago sativa L.) is a perennial forage crop known as the “Queen of Forages.” To dissect the genetic mechanism of flowering time (FT) in alfalfa, high−density linkage maps were constructed for both parents of an F1 mapping population derived from a cross between Cangzhou (P1) and ZhongmuNO.1 (P2), consisting of 150 progenies. The FT showed a transgressive segregation pattern in the mapping population. A total of 13,773 single-nucleotide polymorphism markers was obtained by using restriction-site ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Additionally, RADseq genotyping data were useful in lettuce for identifying molecular markers associated with pest resistance traits to Fusarium wilt race 2 [ 38 ]; a serious cause of yield losses; in soybean; to identify QTLs associated with yield and oil content that could be exploited in MAB strategies through MAB [ 39 ]; and in tomato to reconstruct the population structure of cultivated tomato lines, providing new insights into the Mediterranean long shelf-life germplasm [ 40 ], which could be used to develop new tomato varieties with improved characteristics. In comparison to other molecular PCR-based approaches, the advantages of RADseq consist of having not only the genotype information but also the availability of nucleotide sequences for each of the marker loci analysed, which can then be mapped in the own genome of the species of interest or in those of related ones [ 41 , 42 , 43 ], which provides valuable knowledge for developing fast and efficient targeted PCR-based analytical assays. Moreover, given the high data throughput of the method adopted (1.8 million raw reads per sample; 9351 SNVs and more than 8 thousand RADtags, in the present study), the identification of multiple discriminant alleles for different phenotypes would improve MAS approaches for Mendelian genes and polygenes, or QTLs, by combining multiple information in a single experiment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, RADseq genotyping data were useful in lettuce for identifying molecular markers associated with pest resistance traits to Fusarium wilt race 2 [ 38 ]; a serious cause of yield losses; in soybean; to identify QTLs associated with yield and oil content that could be exploited in MAB strategies through MAB [ 39 ]; and in tomato to reconstruct the population structure of cultivated tomato lines, providing new insights into the Mediterranean long shelf-life germplasm [ 40 ], which could be used to develop new tomato varieties with improved characteristics. In comparison to other molecular PCR-based approaches, the advantages of RADseq consist of having not only the genotype information but also the availability of nucleotide sequences for each of the marker loci analysed, which can then be mapped in the own genome of the species of interest or in those of related ones [ 41 , 42 , 43 ], which provides valuable knowledge for developing fast and efficient targeted PCR-based analytical assays. Moreover, given the high data throughput of the method adopted (1.8 million raw reads per sample; 9351 SNVs and more than 8 thousand RADtags, in the present study), the identification of multiple discriminant alleles for different phenotypes would improve MAS approaches for Mendelian genes and polygenes, or QTLs, by combining multiple information in a single experiment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen from the results that there are some differences between different mapping methods, and the positions of some markers on the genetic map and the physical map are inconsistent. Many plants, such as wheat and alfalfa, also have the phenomenon that the genetic and physical distances between markers on linkage groups are not consistent, mainly because the physical and genetic distances between markers in the repressed and active regions of chromosome recombination are not consistent ( Zhao et al, 2017 ; Jiang et al, 2022 ). After the map construction, using bioinformatics analysis software for the above markers genome distribution of statistical genetic map and genome position corresponding to the relationship between genetic and physical location linear system such as high quality, and the accuracy of assessment to ensure map all indicators show that the research of M. falcata genetic linkage map construction with high quality and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2013) proved the reliability of optimal sequence analysis in M. falcata grazing tolerance, and through morphological index analysis showed that in the Hulunbuir native M. falcata , plant individuals with large projection area, great plant height, significant plants diameters stem number, long root depth and significant root diameters had strong grazing tolerance. Wang (2015) studied the grazing tolerance in Hulunbuir native M. falcata , cloned and analyzed some grazing tolerance-related genes ( Jiang et al, 2022 ). Based on RAD-seq, the genetic linkage map and QTL mapping of Medicago sativa L. flowering stage traits were constructed, and 7 candidate genes related to flowering stage were screened out.…”
Section: Introductionmentioning
confidence: 99%
“…The F1 population consisting of 150 progenies was used for evaluating and identifying loci associated with drought tolerance. Mapping population development, genotyping, and construction of genetic linkage maps were provided in our previous study ( Jiang et al., 2022 ). Briefly, the mapping population was developed by crossing two tetraploid alfalfa plants, Cangzhou (CF000735, paternal parent, P1) and Zhongmu NO.1 (CF0032020, maternal parent, P2).…”
Section: Methodsmentioning
confidence: 99%